The quest for successful internationalization of Bangladesh’s higher education: investigating the strategic leadership characteristics of academic leaders - Mohd Ali, Hairuddin; Zayed, Tareq M (IIUM Press, International Islamic University Malaysia, 2018)
The main purpose of the study is to investigate and determine the underlying factors/constructs of organizational capabilities, personal characteristics of higher education institution administrators and to determine the elements of successful internationalization of higher education institutions in Bangladesh. One thousand and one hundred (1,100) academic leaders were sampled based on two stage multi-stage cluster sampling method. A total of 358 survey questionnaires were successfully returned which were analyzed by SEM statistical tools. The Confirmatory Factor Analysis results showed that organizational capabilities was represented by four distinct factors, personal characteristics represented by three factors, while successful internationalization represented by three factors. The findings implicates the importance of strategic leadership elements endeavors to be focused among the university academic leaders in Bangladesh. The study is considered pertinent particularly in enhancing the strategic leadership literature in Bangladesh’s higher education context.